Cold spots and cold moments: The potential for sediment freezing to depress denitrification in wetland sediments. Issue 5 (13th August 2022) - Gilmour, Kimberly; Hoggarth, Cameron; Williams, Clayton; Baulch, Helen M.
Abstract: Within the north‐temperate zone, winters can be long and are associated with conditions of low temperature and potential for sediment freezing. There are critical gaps in our knowledge of biogeochemical cycling during winter and inadequate knowledge of how warming winters and changing snowpack might affect biogeochemistry. Here, we assessed the impacts of sediment freeze–thaw cycling and nitrate amendment on denitrification rates in the littoral fringe of four urban wetlands. We demonstrate the potential for experimental sediment freezing to suppress denitrification, although freezing effects were not observed at all sites. Multiple freeze–thaw cycles were assessed, and, although subsequent cycles may affect denitrification, the first instance of our experimental freezing seems the most critical. Although this work demonstrates potential sensitivity of wetland denitrification rates to changing winter conditions, we note nitrate availability has a larger impact upon denitrification rates. This suggests nitrification rates and changing nitrate loads may be more important determinants of nitrate retention than sediment freeze–thaw history. Although there has been great interest in hot spots and moments for biogeochemical cycling, we suggest there is similar need to understand cold spots and moments, as evidenced here. This is particularly important where cold moments may correspond with critical periods of nitrate transport, such as snowmelt. Core Ideas: Freezing of urban wetland sediments can suppress denitrification. The number of freeze–thaw cycles may affect nitrate limitation and denitrification. Nitrate availability has a greater impact on denitrification rates than freezing. Sediment freezing is a potential cold moment preceding peak nitrate transport.